Response of quality protein maize (Zea mays) to nutrient and weed management in southern Rajasthan - Owla, M.L.; Nepalia, V.; Singh, Dilip; Mordia, Azad; Sharma, Mahendra (Annals of Agricultural Research, 2016)
A field experiment was conducted during rainy seasons of 2008 and 2009 to evaluate the effect of fertility levels, nutrient sources and weed management on quality protein maize production. The treatments comprised of 3 nitrogen + phosphorus levels viz. 90 + 40, 120 + 50 and 150 + 60 kg N and P2O5 ha–1, 3 nutrient sources viz. 100% NP, 75% NP + 25% vermicompost and 50% NP + 50% vermicompost and 3 weed control measures viz. weedy check, metribuzin 0.4 kg ha–1 followed by hoeing and weeding and atrazine 0.4 kg + alachlor 2.0 kg ha–1 followed by hoeing and weeding (HW). These were tested in a split plot design replicated thrice with nitrogen + phosphorus levels and nutrient sources in main-plots and weed control in sub-plots. Nitrogen + phosphorus levels had no significant effect on weed density, but their dry matter production increased significantly by raising nitrogen + phosphorus level from 90 + 40 kg N and P2O5 ha–1 to 120 + 50 kg N and P2O5 ha–1. The grain yield also increased significantly up to 120 + 50 kg N and P2O5 ha–1 during two years of study (4.20 and 4.15 kg ha–1). Stover and biological yields increased significantly up to 150 + 60 kg N and P2O5 ha–1. Nutrient sources had no significant effect on weed density. Application of 100% NP and 75% NP + 25% vermicompost were at par and significantly superior over 50% NP + 50% vermicompost in producing weed dry matter during both years. Weed management through atrazine + alachlor fb HW resulted in significant reduction in weed density & dry matter with concomitant significant increase in grain, stover & biological yields.